2009
DOI: 10.1007/s10886-009-9653-1
|View full text |Cite
|
Sign up to set email alerts
|

Stigmasterol and Cholesterol Regulate the Expression of Elicitin Genes in Phytophthora sojae

Abstract: Sterol acquisition by soilborne plant pathogens of the genus Phytophthora is presumed to involve extracellular proteins belonging to class-I elicitins. However, little is known about the relationship between sterol availability and elicitin secretion. The objective of this study was to determine the expression of class-I elicitin genes in Phytophthora sojae when grown in a medium containing stigmasterol or cholesterol. P. sojae growth was stimulated by nanomolar concentrations of stigmasterol and cholesterol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Transient assay showed that one of P. capsici elicitin genes ( Pc508761 ) induced plant cell death (Figure 7A). Future studies will involve an exploration of whether these elicitins are required for host infection or sterol acquisition [78].…”
Section: Discussionmentioning
confidence: 99%
“…Transient assay showed that one of P. capsici elicitin genes ( Pc508761 ) induced plant cell death (Figure 7A). Future studies will involve an exploration of whether these elicitins are required for host infection or sterol acquisition [78].…”
Section: Discussionmentioning
confidence: 99%
“…There is the possibility that P. sojae produces and secretes other proteins than just class-I elicitins. However, we previously determined that the most abundant protein in spent filtrates of the organism were class-I elicitins using 2D-PAGE followed by LC-MS analysis (Yousef et al 2009). This was also confirmed in this study by visually inspecting spent filtrates on PAGE (data not shown), in which class-I elicitins were the only proteins detected in spent filtrates after silver staining.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the auxotrophic requirement for sterols combined with the in vitro sterol binding activity of class-I elicitins, it has been hypothesized that elicitins act as shuttles that transport sterols from the environment to the pathogen . Yousef et al (2009) found that nanomolar concentrations of sterols (stigmasterol and cholesterol) caused a down-regulation of class-I elicitin gene expression. This also coincided with a reduction in class-I elicitin protein secretion into the spent broth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sterol biosynthesis sub-branch of the MVA pathway has been identified in animals, fungi, and land plants (Figure 1; Desmond and Gribaldo, 2009;Ruiz-Sola et al, 2016). In contrast, oomycete species in the genera Phytophthora and Pythium are sterol auxotrophs that utilize exogenous sterols from the environment or from host plants to support their growth and development (Marshall et al, 2001;Yousef et al, 2009). Genome analyses revealed that most enzymes of the sterol biosynthesis sub-branch are absent in Phytophthora species, which makes them unable to synthesize sterol independently (Tyler et al, 2006;Dahlin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%